(untitled) (Research, Society and Development, 2022)
Humpback whales Megaptera novaenangliae are cosmopolitan animals found throughout the Atlantic Ocean. In this sense, the present study aimed to evaluate the spatial distribution of sightings of M. novaeangliae in the Coastal Zone of Brazil to describe possible spatial patterns and extent of occurrence of the species. Records of sightings of the species acquired on the open data platform System for Monitoring Marine Mammals – SIMMAM were used. The data underwent a filtering process in which duplicate information, data with inaccurate visual identification of the species, inaccurate locations, sightings with a distance greater than 200 miles from the Exclusive Economic Zone (EEZ) and blocked data were excluded. To analyze the distribution patterns of sightings, the Nearest Neighbor functions (G test), Ripley’s Bivariate function (K test) and the empty space function (F test) were applied. The analyzes were developed with the aid of the Rstudio software version 4.1.1. The data were also submitted to the Kernel density estimator algorithm with application of the quartic function in a radius of 3° with classification by quartiles. A total of 2889 sightings were processed, the spatial models (G, K and F functions) indicated cluster consistency and strong correlation between sighting points. The Kernel density algorithm showed that humpback whales occur from Amapá to Santa Catarina, but with higher concentrations in the Abrolhos Bank region and on the northeast-east continental shelf, these aggregations are related to breeding areas and calf fattening, while the other less concentrated regions probably correspond to the migratory routes of the species. This study presents a descriptive analysis of distribution patterns of M.novaeangliae for the Brazilian coast and aims to contribute to the knowledge about the spatial ecology of the specie.